Smart Halal Destination Ecosystem: The Exploration of Halal Tourism Ecosystem Model - Sumaryadi Sumaryadi; Anang Sutono; Wisnu Rahtomo; Christian Helmy Rumayar; Faisal Fahdian Puksi (Politeknik Pariwisata NHI Bandung, 2020)
Halal tourism has been recorded steadily growing since 2000.growth Globalof Muslim travelers has grown rapidly from 25 million in 2000 to 140 million in 2018, or growing 25% / year. This growth is predicted to continue to increase to 230 million with a turnover of USD 300 billion (4,200 trillion) in 2026. (Mastercard - Crescent Rating, 2019). Currently, halal tourism has become a global mainstream market, not just a niche market. Halal tourism is a current and promising future tourism trend. Efforts to meet the need for Muslim-friendly tourist destinations are a very rational and profitable choice.